2001
DOI: 10.1080/028418501127346260
|View full text |Cite
|
Sign up to set email alerts
|

Optimal timing of post-biopsy MR imaging of the prostate

Abstract: Deferring MR imaging for at least 3 weeks after prostatic biopsy is advisable. T1-weighted images are necessary to rule out false-positive findings caused by post-biopsy hemorrhage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…Even if we deferred the MR examination for more than 3 weeks after biopsy, as it is classically recommended [35,36], 14.1% (130/920) of the prostate sectors showed bleeding artifacts in our study. As expected, these artifacts decreased the accuracy of tumor localization, both on T2w and DCE images.…”
Section: Discussionmentioning
confidence: 49%
“…Even if we deferred the MR examination for more than 3 weeks after biopsy, as it is classically recommended [35,36], 14.1% (130/920) of the prostate sectors showed bleeding artifacts in our study. As expected, these artifacts decreased the accuracy of tumor localization, both on T2w and DCE images.…”
Section: Discussionmentioning
confidence: 49%
“…For those patients who have an underlying coagulopathy or are on warfarin, a prostate biopsy should not be taken until the international normalized ratio has been corrected to < 1.5 [6]. Several studies have reported that the haemorrhaging diminishes with time [1,4,5]. We also noted a statistically significant negative correlation between the sum of the haemorrhage score and the time from the biopsy.…”
Section: Discussionmentioning
confidence: 51%
“…Among these factors, haemorrhaging after biopsy is the most common obstacle to the accurate detection of prostate cancer after a prostatic biopsy. Based on a review of previous reports, some authors recommend deferring MRI for ≥ 3 weeks after a prostate biopsy [1,4]. However, another reported that timing has no significant effect on cancer localization [5].…”
Section: Introductionmentioning
confidence: 99%
“…Transrectal needle biopsy results in periprostatic inflammation, and the potential for bleeding and haematoma [3,4]. In the study of Ikonen et al [5], assessing endorectal MRI after prostate biopsy, 77% of patients had visible haemorrhage after biopsy. These effects diminished after 21 days, with an obvious decrease in the amount of blood by 28 days.…”
Section: Discussionmentioning
confidence: 99%